Awareness and use of soil conservation practices among Iraqi wheat farmers - Kshash, B. H.; Oda, H. K. (International Journal of Agricultural Technology, 2021)
The results showed that 51% and 40.3% of the wheat farmers indicated a medium level of awareness and usage of soil conservation practices respectively. The most aware and used practices were used fertilizer, crop rotation and mixed farming. Respondents within 30-50 years of age had higher mean scores on the soil conservation practices awareness scale, while those cultivated less than 5 ha that higher mean scores on the soil conservation practices use scale. Respondents cultivated more than 10 ha had the lowest mean scores on the soil conservation practices awareness and use scale. It was concluded that Iraqi wheat farmers should be aware of soil conservation practices and the necessity of using them. An appropriate agricultural extension policy can contribute to achieve this based knowledge